Increasing shelf life of fruits, flowers - New Straits Times, Punitha Kumar (2012)
POST-HARVEST technology,including increased shelf life and minimal fruit processing by the Malaysian Agricultural Research and Development Institute (Mardi), has benefited the local horticulture industry.